Discovery of a Novel Insecticidal Peptide with a Cystine-Stabilized α-Helix/α-Helix Motif from the Venom of Scorpion Liocheles australasiae - Masahiro Miyashita; Naoya Mitani; Fuki Iwamoto; Mitsuki Hirota; Yoshiaki Nakagawa (Molecules)
Scorpion venom contains various bioactive peptides, many of which exhibit insecticidal activity. The majority of these peptides have a cystine-stabilized α-helix/β-sheet (CSαβ) motif. In addition to these peptides, scorpion venom also contains those with a cystine-stabilized α-helix/α-helix (CSαα) motif, which are known as κ-KTx peptides. Some of these peptides show weak inhibitory activity on mammal potassium channels, but, in many cases, their biological activity remained unknown. In this study, with the aim of discovering novel insecticidal peptides, we synthesized five peptides, which were predicted to adopt a CSαα motif, identified from the venom of the scorpion Liocheles australasiae, and measured their insecticidal activity. As a result, one of the peptides, named LaIT5, exhibited significant insecticidal activity. To the best of our knowledge, this is the first report of insecticidal peptides with a CSαα motif. Furthermore, we synthesized its analogs based on sequence comparisons with other inactive CSαα-motif peptides to identify amino acid residues important for its insecticidal activity. The results indicate that two consecutive His residues at the central region of LaIT5 are particularly important for the activity. Since LaIT5 did not show any toxicity against mice, it was concluded that its action is selective for insects.